Sacred Imagery and the Sacralisation of Violence in the Martial Arts - David Hugh Kendall Brown; George Jennings; David Sebastian Contreras Islas; Jungjoo Yun; Simon Dodd (Im@go. A Journal of the Social Imaginary, 2022)
Engaging in martial combat, whether for military, self-defence or cultivation purposes, is taken to sensitise practitioners towards existential issues which in turn enliven potential religio-spiritual experiences and awakenings. In this paper, we